Improving the adoption of agricultural sustainability tools: A comparative analysis. (April 2020) - Whitehead, Jay; MacLeod, Catriona J.; Campbell, Hugh
Highlights: Stakeholder involvement alone is not enough to ensure sustainability tool adoption. Tool adoption requires balancing tool functionality and stakeholder involvement. Managerial support from industry leaders is a key determinant of tool adoption. Sustainability assessment tools require a well-defined and supportive end-user base. Abstract: The implementation and ongoing adoption of agricultural sustainability tools are challenging and not well addressed in the literature on sustainability assessment. Co-production of sustainability assessment and reporting systems between researchers and stakeholders has been promoted to increase the successful adoption of sustainability tools. Scientific attention has focused primarily on the development of sustainability assessment tools and has given less attention to the factors that encourage or discourage adoption and implementation. This paper provides ex-post reflections of the critical success factors, barriers, and lessons learned from the development of nine sustainability tools by the New Zealand Sustainability Dashboard Project (NZSDP) over six years of research and across multiple case studies. While the literature suggests that stakeholder participation and tool functionality are critical determinants for the successful adoption of a sustainability tool, this paper finds that neither factor adequately predicted the adoption of a tool. Instead, adoption was found to depend on a range of more nuanced concerns such as managerial support, end-user capability, and the specificity of the tool's functions. In order to ensure that practical outcomes are achieved through sustainability assessment, more attention needs to be given to the factors that enhance or impede sustainability tool adoption.